Filibacter tadaridae sp. nov., isolated from within a guano pile from a colony of Mexican free-tailed bats Tadarida brasiliensis. Issue 5 (20th March 2019) - Kämpfer, Peter; Bizet, Chantal; Clermont, Dominique; Criscuolo, Alexis; Kloepper, Laura N.; Duncan, Makenzie B.; McInroy, John A.; Kloepper, Joseph W.; Schumann, Peter; Glaeser, Stefanie P.
Abstract : A Gram-stain-positive, aerobic bacterium, TB-66 T, was isolated from a pile of bat guano in a cave of New Mexico, USA. On the basis of 16S rRNA gene sequence similarity comparisons, strain TB-66 T grouped together with Filibacter limicola showing a 16S rRNA gene sequence similarity of 98.5 % to the type strain. The quinone system of strain TB-66 T consisted predominantly of menaquinone MK-7. The polar lipid profile contained diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine, phosphatidylmonomethylethanolamine, phosphatidylserine and three unidentified phospholipids. The peptidoglycan type was A4αl -Lys–d -Glu (A11.33). The major fatty acids were C15 : 0 anteiso, C16 : 0, and C16 : 1  ω7c. The G+C content of the genomic DNA was 37.6 (±1.8) mol%. On the basis of the genotypic and phenotypic properties it is clear that strain TB-66 T represents a member of the genus Filibacter, but is distinct from the only other species in the genus, Filibacter limicola DSM 13886 T . We propose a novel species with the name Filibacter tadaridae sp. nov. The type strain is TB-66 T (= CIP 111629 T = LMG 30660 T = CCM 8866 T ).